Development dark chocolate enriched with mangrove leaf powder (Sonneratia alba): Physico-chemical properties, antioxidant activity, and sensory quality - Nizori, Addion; Mursyid, Mursyid; Ananda, Rizki; Latief, Madyawati; Tarigan, Indra Lasmana; humaryanto, Humaryanto; azima, Fauzan; Cahyana, Yana; Budiyanto, Budiyanto; Wazzan, Huda; Seow, Eng Keng (Hasanuddin University Food Science and Technology Study Program, 2025)
The incorporation of mangrove leaf powder into food systems offers an emerging strategy for enhancing the functional value of confectionery products. This study evaluated the effects of Sonneratia alba (S. alba) mangrove-leaf powder on the physicochemical properties, antioxidant capacity, and sensory quality of dark chocolate. Leaves were processed into fine 60-mesh powder and added at concentrations of 0–5.5% (w/w). The analytical assessments included moisture content, total phenolic content (TPC), antioxidant activity using the DPPH method, CIELAB colour parameters, texture hardness, and consumer acceptance. The product underwent enrichment with S. alba produced significant (p < 0.05) increases in TPC (49.06–64.37 mg GAE/g) and antioxidant activity (60.45–69.45%). A strong linear relationship between TPC and DPPH inhibition (R² = 0.934) indicated that phenolics contributed directly to enhanced radical-scavenging performance. Colour measurements showed elevated a* and b* values with increasing leaf concentration, reflecting intensified red–yellow chromaticity from plant pigments. Meanwhile, hardness decreased from 135.33 to 98.95 g/F, suggesting that fibre components disrupted fat crystallisation and softened the chocolate matrix. Sensory evaluation demonstrated that intermediate enrichment levels (4.5%–5.5%) provided the most favourable consumer responses, yielding the highest scores for flavour, texture, and overall acceptance. Collectively, these results indicate that powder from S. alba leaves serves as an effective natural fortifying agent capable of improving the functional profile of dark chocolate without compromising sensory desirability. The findings highlight opportunities to use mangrove biomass as a sustainable, phenolic-rich ingredient for developing clean-label, functional chocolate products.